Action cartoons and their impact on children's aggressive behavior - Husnul Khotimah Shobiroh; Muhammad Yusri Bachtiar; Syamsuardi Saodi (Institut Agama Islam Negeri Langsa, 2021)
Cartoons present a unique attraction for children, and the action genre is one of the television programs that primarily broadcast. Children observe characters in action cartoons and repeat what they see or hear. This study aims to determine whether the effect of aggressive behavior in children when watching action cartoons. The research approach is quantitative. The subject was 12 children aged 5-6 years in the Doa Ibu Kindergarten, Makasar. The researcher used data collection techniques in descriptive statistical analysis and Pearson Product Moment Correlation analysis. The results showed a positive relationship between watching action cartoons and aggressive behavior of children aged 5-6 years and included in the category of moderately influential. To reduce these effects, interventions that must be carried out need to be studied further.